IDENTIFIKASI BAKTERI Eschericia coli SEROTIPE O157 DENGAN MEDIA SORBITOL MAC CONKEY AGAR (SMAC) PADA BUAH SEMANGKA POTONG DARI PEDAGANG BUAH KAKI LIMA DI KOTA DENPASAR - I Made Nugraha Gunamanta Sabudi; Made Agus Hendrayana (E-Jurnal Medika Udayana, 2017)
coli is a bacteria that can cause clinical manifestations from mild to severe diarrhea, especially E. coli serotipe O157 as pathogenic bacterium that can cause bloody diarrhea. Watermelon pieces sold by street vendors is a fruit that is processed in a minimalist way and have a chance contaminated with E. coli in various ways during the cutting process, storage, till packing up to the consumer. Therefore it was important to identify the E. coli serotipe O157 on watermelon pieces sold by street vendors. The aim of study was to determine whether there was E. coli serotipe O157 or not in watermelon pieces that sold by fruit street vendor in Denpasar. The method used TSB grower medium, McConkey, EMBA, SMAC and gram staining to identificate of E. coli serotipe O157 on watermelon pieces samples. The study found five samples showed positive signs of E. coli, and none showed signs of positive E. coli O157 from ten samples. As a conclusion there was no E. coli serotipe O157 showed on watermelon pieces, but found positive E.coli (non serotipe O157) in Denpasar, especially on North, West and East Denpasar Keywords: Identification, E. coli, serotipe O157, Watermelon, Watermelon pieces, fruits street vendors